A novel balanced chromosomal translocation found in subjects with schizophrenia and schizotypal personality disorder: Altered l-serine level associated with disruption of PSAT1 gene expression - Ozeki, Yuji; Pickard, Benjamin S.; Kano, Shin-ichi; Malloy, Mary P.; Zeledon, Mariela; Sun, Daniel Q.; Fujii, Kumiko; Wakui, Keiko; Shirayama, Yukihiko; Fukushima, Yoshimitsu; Kunugi, Hiroshi; Hashimoto, Kenji; et al. (Neuroscience research, 2011)
▶ A novel chromosomal translocation is identified in a patient with schizophrenia. ▶ Decreases in l-serine and glutamate are observed in the sera of the patient and son. ▶ PSAT1 gene expression is reduced in the cells from the patient and her son. ▶ Impaired expression of PSAT1 gene may cause decreased l-serine production. l-Serine is required for the synthesis of glycine and d-serine, both of which are NMDA receptor co-agonists. Although roles for d-serine and glycine have been suggested in schizophrenia, little is known about the role of the l-serine synthesizing cascade in schizophrenia or related psychiatric conditions. Here we report a patient with schizophrenia carrying a balanced chromosomal translocation with the breakpoints localized to 3q13.12 and 9q21.2. We examined this proband and her son with schizotypal personality disorder for chromosomal abnormalities, molecular expression profiles, and serum amino acids. Marked decrease of l-serine and glutamate was observed in the sera of the patient and her son, compared with those in normal controls. Interestingly, expression of PSAT1 gene, which is located next to the breakpoint and encodes one of the enzymes in the l-serine synthesizing cascade, was reduced in both patient and her son. Direct effect of impaired PSAT1 gene expression on decreased serum l-serine level was strongly implicated by rat astrocyte experiments. In summary, we propose an idea that PSAT1 may be implicated in altered serine metabolism and schizophrenia spectrum conditions.